Basics of electrical drives - Pillai, S. K. (New Academic Science, 2015)
"In this book, fundamentals of electrical drives are discussed keeping in mind the students of electrical engineering. Dynamics of electrical drives; characteristics of dc and ac motors while starting, running and braking; determination of rating and heating of motors are described in detail. Drives used in various industries are discussed in a separate chapter 'Industrial Applications'. Solved examples and problems are given at the end of most of the chapters. The book acquaints the students with the recent trends in the development of electric motors used as prime movers in electric drive systems. The chapter on 'Introduction to Solid State Controlled Drives' has been expanded to include sections on increasingly used 'Brushless dc motors' and 'Switched-reluctance motors'. A separate chapter on the more commonly used position control drive motors, namely, 'Stepper Motors' has been also incorporated."--Amazon.in